Self-efficacy and locus of control as predictors of academic achievement among secondary school students in osun state unity schools (2008)
The study investigated self-efficacy and locus of control as predictor of academic achievement among Junior Secondary school students in Osun state Unity schools, using Self-Efficacy Scale (SES) and Locus of Control Scale (LOC) as measuring instruments. The Cronbach alpha coefficient for validity of the two instruments are respectively a = 0.68 and a = 0.83. A descriptive survey research design was adopted using a sample of two hundred (200) students randomly selected from three (3) Government unity schools in Osun state. One hypothesis and two research questions were generated and tested using Analysis of Variance (ANOVA), Pearson Product Moment Correlation Coefficient and Multiple Regression statistical tools with the margin of error set at 0.05 significant levels. The results indicated that a significant relationship exists between self- efficacy, locus of control and academic achievement. The study also revealed that self- efficacy and locus of control predict well students’ academic achievement. Implication of these findings on stakeholders in educational industry, curriculum planners, educational psychologists and practitioners were suggested.